HUBUNGAN ANTARA GRATITUDE DENGAN KETERIKATAN KERJA PADA KARYAWAN PT. BANK ACEH SYARIAH CABANG JANTHO - Feny Ghaisani; Farid Fathony Ashal; Ismail Rasyid Ridha (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2022)
This study was conducted to determine the relationship between gratitude and work engagement on employees of PT. Bank Aceh Syariah Jantho Branch. The study used a quantitative approach based on primary data (through a questionnaire) with a total sample of 42 employees of PT. Bank Aceh Syariah Jantho Branch with saturation sampling technique. Data analysis using Pearson Correlation test. The results showed that the relationship between the variables of gratitude and work engagement showed a positive and strong direction as seen from the correlation value of r 0.762 and there was a significant relationship between gratitude and work attachment to employees, with a significance value of p 0.00 < 0.01, the higher the gratitude possessed employees the higher their work engagement will be. Keywords: Gratitude, Work Engagement, Employees